Efektivitas Integrasi Discovery Learning dan Wordwall Berbasis Deep Learning terhadap Pemahaman Konsep Pecahan - Nur Kharisma Septiyani; Nuhyal Ulia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Understanding fraction concepts remains one of the fundamental mathematical competencies that poses challenges for elementary school students. Students’ low ability to comprehend fraction concepts indicates the need for innovative learning approaches that promote active engagement and deeper conceptual understanding. This study aims to examine the effectiveness of integrating Discovery Learning and Wordwall based on the Deep Learning approach in improving elementary school students’ understanding of fraction concepts. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 48 fourth-grade students of SD Negeri Babadan, divided into an experimental group and a control group. Data were collected through concept-understanding tests administered before and after the intervention and were analyzed using inferential statistical techniques and learning gain analysis. The findings revealed that students who participated in learning through the integration of Discovery Learning and Wordwall based on the Deep Learning approach demonstrated a better understanding of fraction concepts than those who experienced conventional instruction. Furthermore, the implementation of the model contributed to a moderate improvement in students’ conceptual understanding. These findings suggest that the integration of instructional models, deep learning approaches, and interactive digital media can serve as an effective alternative for supporting mathematics learning in elementary schools, particularly in fraction topics.